2020
DOI: 10.1111/jfbc.13516
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, purification, characterization, and immunomodulatory effects of polysaccharide from Auricularia auricula on RAW264.7 macrophages

Abstract: Polysaccharides have many biological functions, such as energy storage substances in organisms, body lubricant, cells that recognize foreign tissues, and basic components of blood group substances, and they are found in almost all organisms (Hu et al., 2018). Research on their isolation, purification, composition, and structure has made extraordinary progress, moreover,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Based on a thorough review of previous literature, it was found that fungal polysaccharides could normally be extracted by HWE method under the following conditions: Extraction time of 2–4 h, extraction temperature of 60–100 ℃, solid-to-liquid ratio of 1:50–1:100 g/mL ( Cai et al, 2015 , Hajji et al, 2021 , Wang et al, 2017 , Wu et al, 2010a ). Udchumpisai and Bangyeekhun, 2019 , Guo et al, 2019 , Bao et al, 2020 , and Ma et al (2016a) prepared an anti-tumor, antioxidant, immunoactive polysaccharides, and a non-toxic polysaccharides by using HWE method, respectively. Yu et al (2017) separated a polysaccharides from Flammulina velutipes with antioxidant activity by UAE under optimized extraction conditions as follows: Ultrasound power of 380 W, extraction time of 25 min, and material granularity of 400-mesh, and the yield of polysaccharide was 20.52 %.…”
Section: Extraction and Purification Methods Of Fungal Polysaccharidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on a thorough review of previous literature, it was found that fungal polysaccharides could normally be extracted by HWE method under the following conditions: Extraction time of 2–4 h, extraction temperature of 60–100 ℃, solid-to-liquid ratio of 1:50–1:100 g/mL ( Cai et al, 2015 , Hajji et al, 2021 , Wang et al, 2017 , Wu et al, 2010a ). Udchumpisai and Bangyeekhun, 2019 , Guo et al, 2019 , Bao et al, 2020 , and Ma et al (2016a) prepared an anti-tumor, antioxidant, immunoactive polysaccharides, and a non-toxic polysaccharides by using HWE method, respectively. Yu et al (2017) separated a polysaccharides from Flammulina velutipes with antioxidant activity by UAE under optimized extraction conditions as follows: Ultrasound power of 380 W, extraction time of 25 min, and material granularity of 400-mesh, and the yield of polysaccharide was 20.52 %.…”
Section: Extraction and Purification Methods Of Fungal Polysaccharidesmentioning
confidence: 99%
“…It was observed that GCP50-1 was an α- d -glucan with the main backbone chain of (1 → 4)-α- d -glucopyranosyl residue. Bao et al (2020) extracted Auricularia auricula polysaccharides (AAPs) by HWE and purified them to obtain three fractions (AAP-I, AAP-II, and AAP-III). AAP-I and AAP-II belonged to the glycoproteins, and only AAP-III belonged to a homogeneous pure polysaccharides.…”
Section: Structural Characteristics Of Fungal Polysaccharidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The yield rate of AAP obtained by hot water extraction was 9.68%. Bao et al (2020) also successfully isolated A. auricula polysaccharide by hot water extraction, which showed that this method was an important method for the extraction of AAP.…”
Section: Resultsmentioning
confidence: 86%
“…RAW264.7 cells were seeded in 24-well plates (5 × 10 5 cells/mL) and incubated for 24 h. Similarly, cells were treated as mentioned in Section 3.6.2 and then the supernatants were collected for analysis by the ELISA kits as per the manufacturer’s instructions [ 43 ].…”
Section: Methodsmentioning
confidence: 99%